DAMPAK ORGANIZATIONAL JUSTICE TERHADAP INNOVATIVE WORK BEHAVIOR: PERAN MEDIASI KNOWLEDGE SHARING - Ayu Intan Amalia; Ardian Prima Putra (Universitas Sarjanawiyata Tamansiswa, 2025)
Based on a report from the Ministry of Cooperatives and Small and Medium Enterprises, a large number of Micro, Small, and Medium Enterprises (MSMEs) have been affected by the pandemic. Of the total, more than half reported a decline in sales, while the rest faced problems related to capital, distribution, and availability of raw materials. This study is a quantitative study with an associative approach conducted through a survey method, aiming to analyze the impact of organizational justice on innovative work behavior, with knowledge sharing as a mediating variabel. Data analysis was performed using PLS-SEM software version 3.0. The measurement tool used in this study was a questionnaire designed with a likert scale, and data were collected from 155 respondents. The sampling technique applied was non-probability sampling with a purposive sampling approach, i.e., sample selection based on specific criteria. The criteria set were respondents who were employees with at least one year of work experience, assuming they had adapted to their jobs. The results of the study indicate that organizational justice has a significant and positive influence on innovative work behavior. Additionally, organizational justice was found to positively contribute to knowledge sharing, and knowledge sharing has a significant and positive influence on innovative work behavior. Other findings show that organizational justice significantly influences innovative work behavior partially through the mediation of knowledge sharing. Keywords: Organizational Justice, Innovative Work, Knowledge Sharing Behavior, Social Exchange Theory(SET), Marketing Employees